2020
DOI: 10.1152/ajpcell.00075.2020
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-3 in the epidermis: more than skin deep

Abstract: The skin is essential for terrestrial life. It is responsible for regulating water permeability and functions as a mechanical barrier that protects against environmental insults such as microbial infection, ultraviolet light, injury, and heat and cold, which could damage the cells of the body and compromise survival of the organism. This barrier is provided by the outer layer, the epidermis, which is composed predominantly of keratinocytes; keratinocytes undergo a program of differentiation to form the stratum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 81 publications
2
93
0
1
Order By: Relevance
“…The dermal water content was reported to be decreased in AQP3-knockout mice [7]. In addition, cutaneous AQP3 is known to change in various skin disorders [25]; for example, AQP3 is decreased in psoriasis [26] and vitiligo [27,28] and during aging [29], causing skin dryness. Furthermore, it was recently found that a decrease in skin AQP3 was involved in the dry skin observed upon treatment with an epidermal growth factor receptor (EGFR) inhibitor [30].…”
Section: Discussionmentioning
confidence: 99%
“…The dermal water content was reported to be decreased in AQP3-knockout mice [7]. In addition, cutaneous AQP3 is known to change in various skin disorders [25]; for example, AQP3 is decreased in psoriasis [26] and vitiligo [27,28] and during aging [29], causing skin dryness. Furthermore, it was recently found that a decrease in skin AQP3 was involved in the dry skin observed upon treatment with an epidermal growth factor receptor (EGFR) inhibitor [30].…”
Section: Discussionmentioning
confidence: 99%
“…Six AQPs are found in the skin, which are distributed to epidermis (AQP1, 3, 7, and 10), dermis (AQP1, 3, and 5), and hypodermis (AQP7) ( Patel et al, 2017 ). Skin AQPs are associated with skin hydration, cell proliferation and differentiation, migration, immunity, and wound healing ( Boury-Jamot et al, 2009 ; Sebastian et al, 2015 ; Bollag et al, 2020 ). Specifically, AQP3 is involved in epidermal cell proliferation and migration; AQP1 controls water movement between blood and dermis to maintain hydration; AQP5, found in both epical and basolateral membranes of the sweat gland is involved in water secretion; AQP7 plays important role to release glycerol from adipocytes for energy production and AQP9 facilitates the transport of glycerol, urea, and H 2 O 2 for defense mechanism ( Patel et al, 2017 ).…”
Section: Tissue-specific Distribution and Physiological Relevance Of mentioning
confidence: 99%
“…Down-regulation and/or mislocalization of AQP3, the most abundant and largely studied aquaglyceroporin in the skin, are associated with psoriasis ( Lee et al, 2012 ; Patel et al, 2017 ; Bollag et al, 2020 ) and vitiligo ( Kim and Lee, 2010 ; Esmat et al, 2018 ). However, although some studies have reported increased mRNA levels of AQP3 in proliferating keratinocytes in psoriasis ( Bowcock et al, 2001 ; Swindell et al, 2014 ), its expression is down-regulated with later differentiation of keratinocytes ( Zheng and Bollinger Bollag, 2003 ).…”
Section: Involvement Of Aquaporins In Non-infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, chronic UV-B irradiation results in loss of hyaluronic acid from the epidermis, thereby contributing to the quiescent phenotype of epidermal keratinocytes. The water- and glycerol-transporting protein AQP3 in the viable epidermis is involved in the mechanisms responsible for various keratinocyte functions including proliferation, hydration, water retention, and barrier function [ 25 , 30 , 33 ]. Various abnormalities in this channel are observed in several skin diseases such as psoriasis and skin cancers [ 33 ].…”
Section: Discussionmentioning
confidence: 99%